Clinical observation of Chinese herbal medicine hot pack therapy combined with meibomian gland massage in the treatment of dry eye of Liver-kidney Yin deficiency and related nursing measures (中药热奄包配合睑板腺按摩治疗肝肾阴虚型干眼症临床观察与护理) - YANG Liu (杨柳); WANG Hao (王浩); YI Qiong (伊琼); YANG Xiufang (杨秀芳) (中西医结合护理)
Objective To investigate the effect of Chinese herbal medicine hot pack therapy combined with meibomian gland massage on relieving uncomfortable symptoms of patients with dry eye of liver-kidney Yin deficiency. Methods Totally 100 patients with dry eye of Liver-kidney Yin deficiency were randomly divided into the study group and control group, with 50 cases in each group. All patients received routine treatment and nursing, and those in the study group were given three course of Chinese herbal medicine hot pack therapy combined with meibomian gland massage. Results The overall effective rate in the study group was higher than that in the control group (98. 00% vs. 70. 00%, P<0. 05). Conclusion The Chinese herbal medicine hot pack therapy combined with meibomian gland massage is potentially effective to relieve uncomfortable symptoms caused by dry eye, and improve the eye condition and recovery of patients. (目的 探讨中药热奄包配合睑板腺按摩对缓解肝肾阴虚型干眼症患者不适症状的效果。方法 选取2020年1月—8月医院收治的100例肝肾阴虚型干眼症患者为研究对象, 采用随机分组方式分为试验组与对照组, 各50例。对照组采用常规治疗方法和护理, 试验组在对照组基础上增加中药热奄包配合睑板腺按摩, 两组均接受为期3个疗程的治疗。对比两组治疗效果。结果 试验组总有效率98. 00%(49/50), 高于对照组的70. 00%(35/50), 差异具有统计学意义(P<0. 01)。结论 中药热奄包配合睑板腺按摩治疗能有效缓解肝肾阴虚型干眼症患者不适症状, 改善眼部情况, 促进康复。)